2018
DOI: 10.1016/j.biomaterials.2018.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Competition of charge-mediated and specific binding by peptide-tagged cationic liposome–DNA nanoparticles in vitro and in vivo

Abstract: Cationic liposome-nucleic acid (CL-NA) complexes, which form spontaneously, are a highly modular gene delivery system. These complexes can be sterically stabilized via PEGylation [PEG: poly (ethylene glycol)] into nanoparticles (NPs) and targeted to specific tissues and cell types via the conjugation of an affinity ligand. However, there are currently no guidelines on how to effectively navigate the large space of compositional parameters that modulate the specific and nonspecific binding interactions of pepti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 84 publications
2
66
0
Order By: Relevance
“…Cationic liposomes (LP) form spontaneous complexes with nucleic acids, which can be sterically stabilized through PEGylation. One study explored the modification of such LPs with CPPs and found that full peptide coverage resulted in less internalization into cells than intermediate coverage, with optimum coverage being cell specific [115]. Additionally, cationic LPs, though effective in vitro, have demonstrated significant cytotoxicity in vivo.…”
Section: Liposomesmentioning
confidence: 99%
“…Cationic liposomes (LP) form spontaneous complexes with nucleic acids, which can be sterically stabilized through PEGylation. One study explored the modification of such LPs with CPPs and found that full peptide coverage resulted in less internalization into cells than intermediate coverage, with optimum coverage being cell specific [115]. Additionally, cationic LPs, though effective in vitro, have demonstrated significant cytotoxicity in vivo.…”
Section: Liposomesmentioning
confidence: 99%
“…Indeed, surface functionalization of metal-based NPs may change the safety profile of NPs (Nel et al 2009;Kubo et al 2018). For example, functionalization of NPs with PEG, chitosan or dextran prevented the opsonization of NPs (i.e., adsorption of biocorona of proteins and other biomolecules onto their surface) and, thus, reduced the uptake of NPs by macrophages and, hence, toxicity (Sheng et al 2009;Jenkins et al 2016;Wonder et al 2018). In contrast, compared with NPs functionalized with neutrally (e.g., with PVP) or negatively charged coatings (e.g., citrate), functionalization of NPs with positively charged groups such as polyethylenimine (PEI), branched PEI or amine group rendered NPs that were more toxic to mammalian cells including murine macrophage cell line RAW264.7 (Líbalová et al 2018), epithelial cells BEAS-2B and human monocytes THP-1 (Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another nanoplatform that holds a great promise for targeted tumor delivery, especially for nucleic acid payloads, is peptide guided cationic liposome nanoparticles [ 61 ]. We studied biodistribution and peritoneal tumor penetration of cRGD and iRGD-targeted polyethylene glycol (PEG)-stabilized cationic liposomes in mice bearing peritoneal carcinomatosis derived from human MKN-45P gastric tumor [ 61 ]. Whereas the IP-dosed untargeted cationic liposomes showed some charge-mediated tumor accumulation, the tumor homing and penetration were increased by functionalization with iRGD or cRGD peptides.…”
Section: Affinity Targeting Of Tumors With Homing Peptidesmentioning
confidence: 99%